A microfluidic platform utilizing anchored water-in-oil-in-water double emulsions to create a niche for analyzing single non-adherent cells. Issue 3 (21st December 2018) - Cai, Bo; Ji, Tian-Tian; Wang, Ning; Li, Xin-Bo; He, Rong-Xiang; Liu, Wei; Wang, Guobin; Zhao, Xing-Zhong; Wang, Lin; Wang, Zheng
Abstract : Water-in-oil-in-water double emulsions (W/O/W DEs) are generated to encapsulate non-adherent cells and anchored in an array on-chip for in situ assays. Abstract : Non-adherent cells play key roles in various biological processes. Studies on this type of cell, especially at single-cell resolution, help reveal molecular mechanisms underlying many biological and pathological processes. The emerging microfluidics technology has developed effective methods for analyzing cells. However, it remains challenging to treat and monitor single live non-adherent cells in an in situ, long-term, and real-time manner. Herein, a microfluidic platform was set up to generate and anchor cell-laden water-in-oil-in-water (W/O/W) double emulsions (DEs) to investigate these cells. Within the device, W/O/W DEs encapsulating non-adherent cells were generated through two adjacent flow-focusing structures and subsequently anchored in an array of microchambers. These droplets maintained the W/O/W structure and the anchorage status in the continuous perfusion fluid for at least one week. The mass transfer of different molecules with suitable molecular weights and partition coefficients between the interior and exterior of W/O/W DEs could be regulated by perfusion fluid flow rates. These features endow this platform with potential to continuously supply encapsulated non-adherent cells with nutrients or small-molecule stimuli/drugs through fluid perfusion. Meanwhile, the confinement of cells in the anchored DEs favored long-term monitoring of cellular dynamic behaviors and responses. As a proof of concept, fluorescein diacetate (FDA) was employed to visualize the cellular uptake and biochemical metabolism of TF-1 human erythroleukemia cells. We believe that this W/O/W DE anchorage and perfusion platform would benefit single-cell-level studies as well as small-molecule drug discovery requiring live non-adherent cells.